COVID-19 planning in United States adolescent sports: a survey of 1880 organizations representing more than 500 000 youth athletes - Haraldsdottir, K.; McGuine, T. A.; Biese, K. M.; Goodavish, L.; Watson, A. M. (Journal of Athletic Training, 2023)
Context High schools and youth sport organizations that restarted participation in the fall of 2020 during the COVID-19 pandemic relied on information sources to develop risk-mitigation procedures.